2022
DOI: 10.1111/cts.13290
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study to evaluate safety, pharmacokinetics, and pharmacodynamics of respiratory syncytial virus neutralizing monoclonal antibody MK‐1654 in healthy Japanese adults

Abstract: Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infection among all infants worldwide and remains a significant cause of morbidity and mortality. To address this unmet medical need, MK-1654, a half-life extended RSV neutralizing monoclonal antibody, is in clinical development for the prevention of RSV disease in infants. This was a phase I, randomized, placebocontrolled, single-site, double-blind trial of MK-1654 in 44 healthy Japanese adults. The safety, tolerability, pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Orito et al. ( 47 ) proved that the bioavailability of MK-1654 in healthy adults was 86% and 77% for the 100 mg i.m. and 300 mg i.m.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Orito et al. ( 47 ) proved that the bioavailability of MK-1654 in healthy adults was 86% and 77% for the 100 mg i.m. and 300 mg i.m.…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference in safety events between the MK1654 and placebo groups. Orito et al (47) proved that the bioavailability of MK-1654 in healthy adults was 86% and 77% for the 100 mg i.m. and 300 mg i.m.…”
Section: Clesrovimab (Mk-1654)mentioning
confidence: 99%
“…It recognizes a quaternary epitope, preferentially binding preF over postF and demonstrating high in vivo potency against subtype A and B RSV 78 . Data are available from testing in healthy adults, and modeling studies predict high levels of protection from LRTI through 150 days at a dose of ≥ 75 mg in infants [79][80][81] . A phase 2b/3 efficacy study in healthy pre-and full-term infants (NCT04767373) is estimated to be completed in 2024, and a phase 3 comparison to palivizumab in high-risk infants (NCT04938830) in 2026.…”
Section: Late-phase and Approved Vaccinesmentioning
confidence: 99%
“…152). An in vitro study showed high potency against RSV-A and RSV-B clinical isolates and low threshold to resistance, but efficacy is largely unknown with only phase I adult data published to date 153,154 . A phase Ib/IIa study showed 80.6% efficacy against medically attended RSV LRTI (unpublished data; see ref.…”
Section: Preventive Strategiesmentioning
confidence: 99%